Ricochet [compact disc] (Loma Vista Recordings, 2025)
"Rise Against return with new album, their most resounding and reinvigorating music to date. Twelve songs, produced by Grammy-winner Catherine Marks and mixed by Alan Moulder, these punk rock pathfinders find a world of constant stimuli, algorithms intended to aggravate and divide. They ask fans to consider who ultimately benefits from this collective division and displeasure. An album massive in sound but centered around the small parts of the psyche that lead to the biggest positive change." -- Provided by publisher